2022
DOI: 10.1101/2022.08.22.22279088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Younger age of initiation of selling sex and depressive symptoms among female sex workers in Eswatini

Abstract: Background: Minors who sell sex are likely to have complex mental health needs that may persist into adulthood. This topic is understudied in Sub-Saharan Africa. This study hypothesized that adult female sex workers in Eswatini who started selling sex as minors have a higher prevalence of depression than those who started as adults. We also examined correlates of depression and underage initiation of selling sex, including stigma and condom-related behaviors. Methods: From October-December 2014, women aged 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Much of the research on underage entry into selling sex has been conducted in Asia [3][4][5][6][7], Eastern Europe [8,9], and the Americas [10][11][12][13][14][15][16][17][18]. A growing body of studies in Africa have included underage participants who sell sex [19][20][21] or reported the prevalence and predictors of underage entry into selling sex among adult female sex workers (FSW) [22][23][24][25][26][27][28]. Research on this topic is particularly important in Africa due to the disproportionate burden of poor sexual and reproductive health outcomes among adolescents in the region [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the research on underage entry into selling sex has been conducted in Asia [3][4][5][6][7], Eastern Europe [8,9], and the Americas [10][11][12][13][14][15][16][17][18]. A growing body of studies in Africa have included underage participants who sell sex [19][20][21] or reported the prevalence and predictors of underage entry into selling sex among adult female sex workers (FSW) [22][23][24][25][26][27][28]. Research on this topic is particularly important in Africa due to the disproportionate burden of poor sexual and reproductive health outcomes among adolescents in the region [29,30].…”
Section: Introductionmentioning
confidence: 99%